Wearable Antennas for Remote Health Care Monitoring Systems - Laura Corchia; Giuseppina Monti; Egidio De Benedetto; Luciano Tarricone (International Journal of Antennas and Propagation)
Remote monitoring of the elderly in telehealth applications requires that the monitoring must not affect the elderly’s regular habits. To ensure this requirement, the components (i.e., sensor and antenna) necessary to carry out such monitoring should blend in with the elderly’s daily routine. To this end, an effective strategy relies on employing wearable antennas that can be fully integrated with clothes and that can be used for remotely transmitting/receiving the sensor data. Starting from these considerations, in this work, two different methods for wearable antenna fabrication are described in detail: the first resorts to the combined use of nonwoven conductive fabrics and of a cutting plotter for shaping the fabric, whereas the second considered fabrication method resorts to the embroidery of conductive threads. To demonstrate the suitability of the considered fabrication techniques and to highlight their pros and cons, numerical and experimental results related to different wearable antennas are also reported and commented on. Results demonstrate that the presented fabrication techniques and strategies are very flexible and can be used to obtain low-cost wearable antennas with performance tailored for the specific application at hand.